Paving Block and Canopy Development of "Sweembath" Tourism Village Realizing Community Welfare - Tugiman; Ariani, Farida; Dardanila; Suwilo, Saib; Tulus; Sartini, Eva; Bayu; Tafsih, Ma'Ruf; Patriani, Peni; Silalahi, Amlys Syahputra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The Sweembath Bahapal baths were built in 1930 by the Dutch government by employing plantation workers. This bathhouse was used as a place of entertainment by the Dutch. Currently, the management of the Sweembath tourism area has been handed over to the local community as the manager of village tourism. The preliminary survey shows the need for further development so that it is expected to improve the welfare of rural communities. Some of the problems that arise are related to the availability of infrastructure and facilities, as well as lack of promotion, which are inhibiting factors for the development of this tourism potential. The objective of the development of the Naga Sopa "Sweembath" Tourism Village, Bandar Huluan District, Simalungun Regency is to create community welfare. These are: Repairing road structuring facilities in the sweembath tourist area to increase the number of tourism visits that can improve the welfare of the community. The results of the activities carried out by USU's LPPM were road arrangement (paving blocks) and construction of a canopy.